Trends and Focus of Research on Suf'ah Rights in Land Purchase and Sale: A Bibliometric Analysis Study - Elfi Sahara; Ahmad Fauzi; Derma Wenni (Saqifah: Jurnal Hukum Ekonomi Syariah, 2025)
The right of syuf'ah is a privilege that is legally granted to certain individuals, usually to the joint owner or closest neighbor of the owner of the land or property to be sold. This right gives priority to the party to purchase the property before it is offered to other parties outside the scope. The main purpose of the existence of the right of syuf'ah is to maintain stability, comfort, and common interests in the surrounding environment, as well as prevent the entry of outsiders who have the potential to disrupt harmony and social order in the area. This study was conducted using a bibliometric approach, namely a method of analyzing scientific literature based on bibliographic data to identify trends, developments, and research patterns in a field of science. To support this analysis, the VOSviewer application is used as a bibliometric data visualization tool, which allows researchers to map the relationship between keywords and the distribution of topics in the relevant literature. Secondary data in this study were obtained through searching for scientific publications on Google Scholar using Publish or Perish software, which was specifically used to collect bibliographic data during the period 2020 to 2025. The results of the analysis show fluctuations in the number of journal publications related to the right of syuf'ah during the period. The peak number of publications occurred in 2022, with a total of 19 scientific articles published. This shows that in that year there was an increase in interest and attention from academics to the issue of the right of syuf'ah. In terms of publishing institutions, the most consistent and productive journal in publishing articles related to this topic is TAFAQQUH: Jurnal Hukum Ekonomi Syariah. In addition, in terms of author contributions, the name Jamaludin, Mohd Hafiz emerged as the most productive author during the research period, with significant contributions to the development of literature in the field of syuf'ah law.